Cell Fate Decisions in the Wake of Histone H3 Deposition - Franklin, Reuben; Murn, Jernej; Cheloufi, Sihem (Frontiers in Cell and Developmental Biology, 2021)
An expanding repertoire of histone variants and specialized histone chaperone partners showcases the versatility of nucleosome assembly during different cellular processes. Recent research has suggested an integral role of nucleosome assembly pathways in both maintaining cell identity and influencing cell fate decisions during development and normal homeostasis. Mutations and altered expression profiles of histones and corresponding histone chaperone partners are associated with developmental defects and cancer. Here, we discuss the spatiotemporal deposition mechanisms of the Histone H3 variants and their influence on mammalian cell fate during development. We focus on H3 given its profound effect on nucleosome stability and its recently characterized deposition pathways. We propose that differences in deposition of H3 variants are largely dependent on the phase of the cell cycle and cellular potency but are also affected by cellular stress and changes in cell fate. We also discuss the utility of modern technologies in dissecting the spatiotemporal control of H3 variant deposition, and how this could shed light on the mechanisms of cell identity maintenance and lineage commitment. The current knowledge and future studies will help us better understand how organisms employ nucleosome dynamics in health, disease, and aging. Ultimately, these pathways can be manipulated to induce cell fate change in a therapeutic setting depending on the cellular context.